تقييم برامج التكوين المهني لمعلمي التربية الخاصة في مؤسسات ومراكز التربية الخاصة في الأردن - الخطيب، عاكف عبدالله موسى; القاضي، هيثم ممدوح قفطان (جامعة تشرين, 2016)
هدفت البحث إلى تقييم برامج التكوين المهني لمعلمي التربية الخاصة في مؤسسات ومراكز التربية الخاصة من وجهة نظرهم، كما هدفت إلى التعرف على أثر متغيري الخبرة ونوع المدرسة على درجة توافر برامج التكوين المهني. وتكونت عينة البحث من (60) معلما ومعلمة، ولتحقيق أهداف البحث تم بناء استبانة تكونت من (74) مؤشرا موزعة على أربعة أبعاد رئيسة. وأظهرت النتائج أن هناك بعدا واحدا ذا درجة تطابق مرتفعة، وهو: بعد "أهداف برنامج التدريب المهني" بمتوسط حسابي بلغ (2.55)، في حين وجود ثلاثة أبعاد رئيسة تطابقت بدرجة متوسطة، وهي على التوالي: بعد "سمات وخصائص المدربين" بمتوسط حسابي مقداره (2.23)، وبعد "محتوى البرامج ومضامينها" بمتوسط حسابي (2.12)، وبعد "الجانب الإداري والتنظيمي" في المرتبة الأخيرة وبمتوسط حسابي بلغ (2.00)، وبلغ المتوسط الحسابي للدرجة الكلية لأبعاد الاستبانة، (2.25). كما أظهرت النتائج عدم وجود فروق ذات دلالة إحصائية (α = 0.05) تعزى لأثر الخبرة في جميع الأبعاد وفي الدرجة الكلية. في حين أشارت نتائج البحث إلى وجود فروق ذات دلالة إحصائية عند مستوى (α = 0.05) تعزى لأثر نوع المؤسسة.
The study aimed at evaluating the professional formation programs for the teachers of special education during service in the institutions and centers of special education in Jordan. It also aimed at determining the effect of the variables of experience and school type on the degree of obtaining professional formation programs. The study sample consisted of (60) male and female teachers. To achieve the purpose of the study, a tool was designed and consisted of (74) indicators distributed into four major dimensions. The results showed that there was one dimension with a high application degree, which is '' the objectives of the professional training programs'' with a mean of (2.55) whereas there were three main dimensions applied in a medium degree; they are as follows: the dimension of trainers’ characteristics, with a mean of (2.23); the dimension of programs’ content, with a mean of (2.12); and the dimension of organizational and administrative aspect, with a mean of (2.00) which ranked finally. The total mean of the tool dimensions was (2.25). The result also showed statistically significant differences at (alpha = 0.05) due to experience in all dimensions and the total degree. However, there were statistically significant differences at (alpha = 0.05) due to institution type.
Keywords: معلمو التربية الخاصة -- التدريب المهني -- الإدارة التعليمية -- الأردن